CHARACTERIZATION OF BENTHIC ANIMAL RESOURCES AT THE DE GI LAGOON, BINH DINH PROVINCE - Ngai, Phan Duc; Tuan, Vo Si; Long, Nguyen Van; Tuyen, Hua Thai; Hong, Phan Thi Kim (Vietnam Journal of Marine Science and Technology, 2015)
The characterization of the benthic animal resouces at the De Gi lagoon was determined by four investigations and surveys from 2009 - 2011 and 2015. The results have pointed out 10 benthic animal species that have primarily economic value at the De Gi lagoon including: 5 Bivalvia species, 1 Gastropoda species, 4 Crustacea species. Bivalve group possesses 64% of the entire commercial yield of benthic animal (1,037.5 tons/year), Gari elongata possesses 71% of the entire bivalve yield and possesses 45% of the entire commercial yield of benthic animal. The seed yield of bivalves group (Crassostrea cf. lugubris) possesses 87% of the entire seed yield of benthic animal (4,133,600 individuals/year). Penaeus monodon is the special benthic animal resource of De Gi lagoon. The majority of benthic animal resources are epifauna, inhabit tidal area and concentrate in sandy tidal flats. The results of this study will provide the scientific basis for further studies on the trophic relationship, food web and data for planning, zoning and appropriate priexploitation of fisheries resources.